Analisis Transitivitas Teks Takepan Banyuurung dan Relavansinya terhadap Pembelajaran Sastra - Haer, Zul; Suryanirmala, Neni; Yunus, Muhamad (Lembaga Yasin AlSys, 2023)
The problem studied in this study is the transitivity analysis of Banyuurung text. Based on the logic of this problem, it is also the problem in this study that describes the transitivity system and its relevance to learning literature in schools. The approach used in this study is descriptive qualitative and based on the theory of Systemic Functional Linguistics (LFS). The method of data collection is done through documentation of transcripts, studies, and notes as a technique. The data analysis was carried out using identification techniques and the results of data analysis used the description method, describing and describing the data that had been collected or existed. The research findings show that the transitivity system in Banyuurung text (mental process) is 60 %) and the process of being is 60%. In addition to the process of being, goals, actors, behavior, phenomena, sensing with a total of 20%.